DEVELOPMENT OF FATIGUE ANALYSIS METHOD FOR LONG-SPAN CABLE-STAYED BRIDGES (CASE STUDY : PULAU BALANG BRIDGE) - Ilyas Pratama, Nuriana
The Pulau Balang Bridge is a cable-stayed bridge connecting Balikpapan to the New Core Government Center in East Kalimantan. This bridge is of utmost importance and is projected to experience very heavy traffic, with a variety of vehicle types. Therefore, an evaluation is needed to assess the existing bridge conditions to withstand dynamic and repetitive loading. One evaluation that can be conducted is fatigue evaluation. However, fatigue evaluation for cable structures of cable-stayed bridges is not yet available in Indonesia, thus necessitating the development of fatigue analysis. The research method begins with modeling the bridge using Midas Civil 2022 software. The model is statically and dynamically validated against loading test loads. Prior to fatigue analysis, a Parametric Study is required to observe the bridge's behavior under various influence line variations, vehicle loading types, and vehicle spacing to determine stress range values. Fatigue analysis begins with loading based on SNI 1725:2016, AASHTO LRFD 2020, Eurocode 1991-2 (2003), and finally using Weigh in Motion (WIM) loading. Fatigue analysis is conducted using several methods. For SNI, AASHTO, and Eurocode, AASHTO MBE 2018 and Shigley & Mishcke formula are used, while for WIM, AASHTO MBE 2018 and cumulative fatigue damage are utilized. Based on various analyses conducted in the research, several main conclusions can be drawn. First, according to the fatigue limit analysis results, all codes (SNI 1725:2016, LRFD 2020, Eurocode 1991-2(2003), and WIM) remain below the threshold limit, thus implying a fatigue life exceeding 2,000,000 cycles with a lifespan exceeding 75 years. Second, in terms of fatigue strength analysis, the most critical fatigue life and number of cycles are found in the cumulative fatigue damage method, which are 41.30 years and 2,123,281 cycles, respectively. However, this condition arises due to the dominance of trucks (81.19% of total vehicles) with over dimension over loading (ODOL) of 31.47% on the Jakarta Outer Ring Road 54+20B. Upon reducing the vehicle load by 25%, the fatigue life is estimated to be 152.24 years with a total of 7,827,059 cycles. Third, a contradiction arises from the fatigue limit analysis compared to the fatigue strength analysis. This contradiction is marked by the number of cycles exceeding 2,000,000, yet the cable lifespan is less than 75 years. This discrepancy occurs because the number of WIM cycles occurring in one day is 141 cycles (3,855,964 in 75 years or 5,141,285 cycles in 100 years), indicating that the 2,000,000 cycle limit based on PTI or AASHTO LRFD 2020 is not suitable for traffic in Indonesia. Development method is conducted using a combination of AASHTO MBE 2018 formula and Eurocode FLM 4 loading with a vehicle spacing of 3m. By using a load combination of 1.2, the fatigue life result is obtained as 41.72 years with 2,145,174 cycles. This result is close to the previous cumulative fatigue damage result (without reduction), hence the conclusion can be drawn that the development method is applicable.